Disfunción cognitiva postoperatoria - Brunet L., Luis; Penna S., Antonello (Revista Hospital Clínico Universidad de Chile, 2017)
Cognitive function may decline after surgical procedures. Cognitive postoperative dysfunction(CPOD) is subtle and requires neuropsychological test for diagnosis. Multifactorial in origin,its cause is unknown but associated with different risk factors, which especially affects originpeople submitted to extense surgery. CPOD is transient, but in some cases is prolonged andis associated with an increase in mortality and permanente disability. The aging populationand the increase of elderly patients requiring surgery a cause of concern. Clinical studies arerequired to recognize preventive and therapeutic measures to reduce CPOD in the future.